Viabilidad financiera para la creación de la fundación proartico para los artesanos del municipio de Usiacurí (2015)
The general purpose of this project is to determine financial viability for the creation of the Foundation Proartico in favor of the craftsmen of Usiacurí's Municipality in Colombia. By compilation of the initial information, the problem statement is built by analyzing the differents reference frames: of precedents, theoretical, conceptual, historical and legal; in addition, there are defined the technologies of study and analysis of the information. On the other hand, the market research is oriented by the political, economic, cultural, environmental and technological factors; it’s made Fundación Proartico’s SWOT matrix and after that, it’s defined the objectives, market strategies and tactics that will be applied in order to reach the goals of the project and increase the demand of the products made by the Usiacuri’s handicraftsmen. Finally, after elaborating the financial analyses corresponding to the projections of sales, costs and expenses of the operation, it’s determined that the execution of the Foundation Proartico is viable; it is confirmed that the crafts are an attractive product for the consumer market, which is not necessary the modification or improvement of the product to generate expectations on the final client; only it is necessary to improve the strategy of marketing handled nowadays to regional and national level.